Impact of mobile money adoption on financial inclusion for citizens of Metropolitan Lima in 2024 - Pinedo Guzmán, Shirley Alexia; Aldazabal Marticorena, Linda Ariana; Jauregui Arroyo, Ralphi Ricardo; Azabache Moran, Carlos Alberto; Yong Chung, Felipe Eduardo; Moscoso Cuaresma, Julio Ricardo (LACCEI, 2025)
This study analyzes the influence of mobile money usage on financial inclusion among citizens of Metropolitan Lima in 2024. A quantitative methodology was employed, featuring an explanatory and cross-sectional design, with surveys conducted on 254 randomly selected residents. Statistical techniques such as exploratory and confirmatory factor analysis, along with partial least squares structural equation modeling (PLS-SEM), were applied to assess the relationship between mobile money and financial inclusion. The findings reveal that mobile money has a positive and significant impact on financial inclusion, accounting for 61.7% of its variability. Therefore, it is concluded that this technology serves as a strategic tool for overcoming traditional barriers and facilitating access to financial services in urban populations.